Moral Uncanny Valley revisited – how human expectations of robot morality based on robot appearance moderate the perceived morality of robot decisions in high conflict moral dilemmas - Laakasuo, Michael (Frontiers in Psychology, 2023)
In recent years a new sub-field of moral psychology has emerged: moral psychology of AI and robotics. In this field there are several outstanding questions on how robot appearance and other perceived properties of the robots influences the way their decisions are evaluated. Researchers have observed that robot decision are not treated identically to human decisions, even if their antecedents and consequences are identical to human decisions. To study this moral judgment asymmetry effect further, two studies with a series of high conflict moral dilemmas were conducted:Study 1 -which used photorealistic full body imagery --revealed that utilitarian decisions by human or non-creepy (i.e., nice) looking robotic agents were less condemned than "creepy" (i.e., unease inducing) robots, whereas "creepy" robots received higher moral approval when making deontological decisions. Furthermore, an exploratory analysis demonstrated that the creepiest robot did not cause moral surprise or disappointment when making utilitarian decisions. However, Study 2 showed that mere symbolic representation of the agent's face did not trigger the Moral Uncanny Valley (where decisions of creepy robots are perceived negatively), suggesting that the effect is dependent on the photorealistic appearance of the agent. These results are in tension with some previous findings in robot moral judgment literature. Future research should focus on creating standardized stimuli for studying moral decisions involving robots and elucidating the complex interactions between agent appearance, decision type, and pre-decision expectations. This work deepens our understanding of the relationship between a decision-making agent's appearance and the moral judgment of their decisions. The findings have significant implications for the design and implementation of autonomous agents in morally charged situations.